Reckless driving promotion and prevention: priming effects. Issue 2 (27th November 2017) - Lemarié, Linda; Chebat, Jean-Charles; Bellavance, François
Abstract : Purpose: This paper aims to examine how reckless driving scenes in action movies affect young male drivers' perception of reckless drivers and proposes a targeted social marketing strategy to counteract this effect. Design/methodology/approach: The hypotheses were tested through a 2 (reckless driving scenes vs control) × 2 (road safety advertising vs control) online experiment with 151 young male drivers. Findings: Reckless driving scenes in action movies prime a positive image of reckless drivers which impacts young male drivers' attitudes and reckless driving intention. However, a road safety message specifically addressing the positive image of reckless drivers efficiently counteracts this effect. Research limitations/implications: A few studies have experimentally tested the impact of reckless driving promotion on young drivers' attitudes and intention, but none have analysed this impact in terms of the development of a positive image of reckless drivers. In addition, this study emphasises that a targeted message based on social norms can cancel the effect of reckless driving promotion and have a beneficial impact on the most risk-prone drivers. Practical implications: Social marketers working in the field of road safety can improve the efficacy of their social marketing programmes by taking into consideration the positive image of reckless drivers promoted by the media. Social implications: Practitioners should develop interventions and targeted messages that help young drivers cultivate a less idealised and masculine social image of reckless drivers. Originality/value: This paper enhances the awareness of the effect that the media's positive depiction of reckless drivers can have on the youth and proposes a strategy to counteract this effect.